Deficiency in endogenous modulation of prolonged heat pain in patients with Irritable Bowel Syndrome and Temporomandibular Disorder - King, Christopher D. (2009)
Females with Irritable Bowel Syndrome (IBS) and Temporomandibular Disorder (TMD) are characterized by enhanced sensitivity to experimental pain. One possible explanation for this observation is deficiencies in pain modulation systems like Diffuse Noxious Inhibitory Control (DNIC). In a few studies that used brief stimuli, chronic pain patients demonstrate reduced DNIC. The purpose of this study was to compare sensitivity to prolonged heat pain and the efficacy of DNIC in controls to IBS and TMD patients. Heat pain (experimental stimulus; 44.0-49.0°C), which was applied to left palm, was continuously rated during three 30-second trials across three separate testing sessions under the following conditions: without a conditioning stimulus; during concurrent immersion of the right foot in a 23.0°C (control); and during noxious cold immersion in a (DNIC; 8.0-16.0°C) water bath. Compared to controls, IBS and TMD patients reported increased sensitivity to heat pain and failed to demonstrate pain inhibition due to DNIC. Controls showed a significant reduction in pain during the DNIC session. These findings support the idea that chronic pain patients are not only more pain sensitive and demonstrate reduced pain inhibition by pain, possibly because of dysfunction of endogenous pain inhibition systems.